Offensive Performance and Its Relationship to Selected Physiological Variables among Youth Handball Players - مظلوم حيدر سلمان; قاسم دينا حمود; كردي همام فاضل (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The nature of all performance requirements for handball skills, including offensive skills, is linked to a wide range of variables. These variables must be compatible with the players’ abilities, which are linked to physiological variables that force players to face different situations in play. These variables contribute to addressing the most important problems they encounter in play. The more these variables are present, the easier it is for a player to perform and compete at a high level. The importance of this research stems from the researchers’ attempt to understand the offensive performance and some physiological variables of young handball players and to understand the relationship between them. This is an attempt by the researchers to develop tests for coaches to assist them in the training process, in order to select their players according to these tests. Although offensive performance is linked to skill and tactical aspects, it is greatly influenced by the physiological state of the players. Hence, the need to study the relationship between offensive performance and some physiological variables in young handball players emerges, in order to gain a deeper understanding of the influencing factors and achieve systematic development in training. The most important objectives are to determine the relationship between offensive performance and some physiological variables in young handball players. Survey and correlational studies, which are among the most important methods of the descriptive approach, were used. The application sample included (48) players, representing (50%), and (10) survey players, representing (10.42%). The most important conclusions are the existence of a correlation between offensive performance and some physiological variables in young handball players. The most important recommendations are to benefit from these tests and apply them to handball players and samples in other categories. Tests of offensive performance and some physiological variables were made available to coaches of the Iraqi Central Handball Federation and researchers to accurately test their samples.